E-048 Antithrombotics for emergent stenting in acute stroke. (23rd July 2022) - Lahoti, S; Limaye, K; Zevallos, C; Dlouhy, K; Hayakawa, M; Samaniego, E; Hasan, D; Ortega, S; Derdeyn, C
Abstract : Background: Prospective studies have indicated that stenting of extracranial internal carotid artery with thrombectomy of intracranial occlusion has better outcome compared to other approaches for treatment of stroke due to tandem occlusion. However, there is dearth of data on use of anti-thrombotics for stents deployed in emergent setting with no prior adequate antiplatelet therapy. Stent occlusion and intracranial hemorrhage are two major competing risks for use of antithrombotic therapy. We prospectively studied use of tirofiban to balance the two risks in patients who required stent deployment for treatment of acute ischemic stroke. Tirofiban is a reversible GPIIb/IIIa receptor antagonist with rapid onset and offset of action which provides for immediate antiplatelet activity to prevent stent occlusion that can be reversed relatively quickly in case of hemorrhage or need for hemicraniectomy. Methods: Consecutive patients of acute ischemic stroke treated at University of Iowa Hospital from November 2020 with an extracranial or intracranial stent were enrolled in the study. Tirofiban continuous infusion, without bolus dose at a rate of 0.1mcg/kg/min was started shortly prior to deployment of the stent. Head imaging, preferably MRI was obtained as soon as possible after the procedure. Dual oral antiplatelet therapy was started if there was no evidence of intracranial bleed or large infarct which could require hemicraniectomy. Alternatively, tirofiban was continued until an hour before hemicraniectomy or end of 'hemicraniectomy watch' period. Follow-up evaluation was done in the clinic after 3 months with non-invasive vessel imaging. Results: Twenty patients met the study criteria. Seventeen had extracranial and three had intracranial stent placement. Seven patients had received intravenous thrombolytic therapy with alteplase. Stent occlusion occurred in two out of twenty patients (10%) while symptomatic intracranial hemorrhage occurred in one patient (5%). There were confounding factors in both cases of stent occlusion, chronic carotid occlusion in one and incomplete stent expansion in the other. Intracranial hemorrhage occurred in one patient, 36 hours after the procedure and 30 hours after tirofiban was stopped and oral dual antiplatelet therapy was started. Modified Rankin Scale at three months was available for 15 patients, 6/15 (40%) had score of < 2 while 9/20 (45%) had score < 2 at discharge. Two patients died and one pursued hospice care due to causes unrelated to stroke. Intravenous thrombolytic therapy or prior antithrombotic use had no association with stent occlusion. Single patient who had symptomatic intracranial hemorrhage did receive tPA. All three intracranial stents were patent and had no complication. None of the twenty patients had any extracranial hemorrhage. Conclusion: Tirofiban continuous infusion is a safe and possibly effective strategy for emergent stenting in acute ischemic stroke. Disclosures: S. Lahoti: None. K. Limaye: None. C. Zevallos: None. K. Dlouhy: None. M. Hayakawa: None. E. Samaniego: None. D. Hasan: None. S. Ortega: 2; C; Medtronic, Stryker Neurovascular, Microvention. C. Derdeyn: 1; C; Siemens Healthineers. 4; C; Euphrates Vascular, Inc. 6; C; DSMB: Penumbra (MIND), NoNO (ESCAPE NA1 and FRONTIER).